Decoding Silymarin: A Multi-Omics Blueprint for Precision Hepatoprotection - Kalra, Garima (Translational Research in Veterinary Science, 2025)
The global health burden of liver diseases, spanning metabolic dysfunction-associated steatotic liver disease (MASLD), cirrhosis, and hepatocellular carcinoma, has catalysed an intensive search for effective hepatoprotective agents. Traditional Chinese Medicine (TCM) and other herbal systems have long utilized botanical extracts, with Silybum marianum (milk thistle) emerging as a premier candidate for modern pharmacological validation. However, the intrinsic complexity of herbal medicines, characterized by a multi-component and multi-target nature, presents a significant challenge to conventional "single-drug, single-target" research paradigms. The period from 2016 to 2026 marks a transformative decade in which multi-omics integration—encompassing transcriptomics, proteomics, metabolomics, and lipidomics—has become the standard for decoding the scientific connotation of these ancient remedies. The evolution of hepatoprotective research now emphasizes the dynamic interplay between exogenous phytochemicals and endogenous metabolic networks. While silymarin, the standardized extract of S. marianum, has been used for decades, recent methodological advances have revealed that its efficacy is not merely the result of general antioxidant activity but involves highly specific molecular "switches" in lipid metabolism and cellular homeostasis. These insights are driven by a convergence of high-resolution analytical chemistry, sophisticated computational embedding frameworks, and emerging spatial biology techniques. Acknowledgement This research is financed and supported by the scientific project NCN-OPUSLAP (UMO-2021/43/I/NZ9/02612) entitled: Multilevel molecular analysis of the hepatoprotective effect of medicinal herbs extracts in prevention of liver dysfunction caused by aflatoxin B1 in pig as an animal model (in-vivo), and hepatocyte cell culture analysis in human and pig (in-vitro).